Cashless civilization, e-wallets, and acceptance: evidence from low-income group in West Malaysia / Rohaiza Kamis, Shafinar Ismail and Nur Hayati Abd Rahman - Kamis, Rohaiza; Ismail, Shafinar; Abd Rahman, Nur Hayati (Universiti Teknologi Mara Cawangan Pulau Pinang, 2024)
The emergence of e-wallets is expected to align with the worldwide shift towards cashless payment solutions in a post-pandemic era characterized by flourishing digital payments and e-commerce transactions. Cashless payments made with e-wallets have additional benefits over traditional payment methods, which encourage consumers to use the technology more frequently. However, despite their rapid development, e-wallets are still not widely accepted by consumers in Malaysia, and their poor (global) diffusion rates run counter to the claimed benefits provided by technology. The objective of this study is to examine the determinants that affect the level of acceptance of electronic wallets among low-income populations in West Malaysia, who play a vital role in facilitating the transition to a society that relies less on cash transactions. The study utilized a theoretical framework that incorporated an expanded version of the Technology Acceptance Model Theory (TAM). This framework included two extra factors, trust and social influence, to investigate their influence on the acceptability of electronic wallets. Data were gathered via an online self-administered survey from 265 low-income earners in West Malaysia. Eligible respondents reported prior experience with e-wallets and a monthly household income of less than RM4,850. Data analysis was conducted using Partial Least Squares Equation Structural Modelling (PLS-SEM). The findings indicate that the concepts of perceived ease of use and trust have a significant impact on the acceptability of e-wallets. However, it is noteworthy that the social influence factor does not seem to have a substantial impact. This implies that e-wallet users may have reservations about the ease of use and effectiveness of ewallets and may be not ready to accept until they provide a smooth user experience. The study provides significant data that can motivate both ewallet providers and regulators to enhance the quality of e-wallet services. This study acknowledges its limitations and recommends that future research efforts consider the recommendations made to deepen our understanding of this field.